A method of constructing maximin distance designs. (29th October 2020) - Li, Wenlong; Liu, Min-Qian; Tang, Boxin
Summary: An attractive type of space-filling design for computer experiments is the class of maximin distance designs. Algorithmic search is commonly used for finding such designs, but this approach becomes ineffective for large problems. Theoretical construction of maximin distance designs is challenging; some results have been obtained recently, often using highly specialized techniques. This article presents an easy-to-use method for constructing maximin distance designs. The method is versatile as it works with any distance measure. The basic idea is to construct large designs from small designs, and the method is effective because the quality of large designs is guaranteed by that of small designs, as evaluated by the maximin distance criterion.